Women's emotional and sexual attraction to men across the menstrual cycle. (13th October 2017) - Shimoda, Rei; Campbell, Anne; Barton, Robert A
Abstract : Have women evolved to shift their attraction to particular types of men at peak fertility? Methodological issues, which we address in this article, have led to empirical disagreement. We investigate women's attraction for men in relation to the women's cycles. Our results suggest that women's sexual desire is not strictly dependent on cyclic hormonal changes, and are more consistent with a nonadaptive by-product of hormone levels. Abstract: There is ongoing debate about how and why the menstrual cycle affects women's attraction to men. According to the dual sexuality hypothesis, women form pair-bond relationships with men who provide care but also obtain genetic benefits by biasing mating effort towards men with high-fitness genes during the fertile phase. By contrast, the commitment hypothesis proposes that attachment bonds with primary partners function to strengthen pair-bond relationships by enhancing in-pair attraction at the fertile phase, rather than extrapair attraction. We tested these hypotheses by measuring women's daily sexual and emotional attraction towards men over the whole menstrual cycle. We employed 1) a urinary luteinizing hormone test to determine the day of ovulation, 2) a 5-part classification of menstrual cycle that identifies a distinct peri-ovulatory phase, and 3) individualized phase identification for each participant. There was a mid-cycle rise in extrapair sexual desire. Women gave and received more care from partners during the menstrual than the mid-cycle phases. Partner's sexual attractiveness and mutual commitment did not moderate these findings. The results do not support either the dual sexuality or commitment hypotheses, and imply that female self-reported sexual desire is not strictly dependent on cyclic hormonal changes. Our results are more consistent with a recently proposed `spandrel' hypothesis, positing cycle phase effects as a nonfunctional by-product of raised estradiol. Additionally, we found that, with the date of ovulation estimated by luteinizing hormone tests, 45% of ovulations were misclassified by the backward counting method, which urges caution in interpreting results based on counting methods.